1998
DOI: 10.1104/pp.117.4.1227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Functional Homolog of the Yeast Copper Homeostasis Gene ATX1 from Arabidopsis1

Abstract: A cDNA clone encoding a homolog of the yeast (Saccharomyces cerevisiae) gene Anti-oxidant 1 (ATX1) has been identified from Arabidopsis. This gene, referred to as Copper CHaperone (CCH), encodes a protein that is 36% identical to the amino acid sequence of ATX1 and has a 48-amino acid extension at the C-terminal end, which is absent from ATX1 homologs identified in animals. ATX1-deficient yeast (atx1) displayed a loss of high-affinity iron uptake. Expression of CCH in the atx1 strain restored high-affinity iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(179 citation statements)
references
References 36 publications
3
170
0
6
Order By: Relevance
“…Metallochaperones responded differentially to low Cu levels in accordance to their function. For example, CCH (copper chaperone), a plantspecific chaperone, 34 was overrepresented under low vs. high Cu conditions, whereas under our experimental conditions, CCS (Cu chaperone for Cu/ZnSOD and the only chaperone for both cytosolic and chloroplastic Cu/ZnSODs) 35,36 was overrepresented under high vs. low Cu conditions (Fig. S3, ESI †).…”
Section: Gene Expression Changes Under Conditions Of Different Cu Avamentioning
confidence: 78%
“…Metallochaperones responded differentially to low Cu levels in accordance to their function. For example, CCH (copper chaperone), a plantspecific chaperone, 34 was overrepresented under low vs. high Cu conditions, whereas under our experimental conditions, CCS (Cu chaperone for Cu/ZnSOD and the only chaperone for both cytosolic and chloroplastic Cu/ZnSODs) 35,36 was overrepresented under high vs. low Cu conditions (Fig. S3, ESI †).…”
Section: Gene Expression Changes Under Conditions Of Different Cu Avamentioning
confidence: 78%
“…CCH copper chaperones have been identified in Arabidopsis (Himelblau et al, 1998), with four genes encoding proteins predicted to be localized to plastids (Wintz and Vulpe, 2002). The experiments performed in this study were conducted in the absence of any added ATP and copper chaperones, thus making it improbable that this protein is a candidate for the Cu 21 transport activity we see in these thylakoid membrane preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The homolog in yeast (Saccharomyces cerevisiae) ATX1 has been well characterized (Lin and Culotta, 1995;Lin et al, 1997;Pufahl et al, 1997) and found to be involved both in Cu homeostasis by specifically delivering Cu to heavy metal P-type ATPases and in defense against oxidative stress. When overexpressed in a yeast strain lacking the superoxide dismutase gene SOD1, both At-ATX1 and At-CCH can protect the mutant from active oxygen toxicity in a Cu-dependent manner (Himelblau et al, 1998;Puig et al, 2007). In our experiments, expression of NaKR1 or the C-terminal region alone (containing the HMA domain) failed to complement the reactive oxygen toxicity phenotype of yeast sod1D mutant (see Supplemental Figure 2 online), indicating that the HMA domain of NaKR1 functions differently than At-ATX1/ At-CCH when expressed in yeast.…”
Section: Nakr1 Encodes a Heavy Metal Coordinating Proteinmentioning
confidence: 99%
“…HMA domain proteins have been identified in the phloem sap of Brassica napus and Cucurbita maxima (Giavalisco et al, 2006;Lin et al, 2009). In Arabidopsis, HMA domain protein CCH is found in the phloem and is thought to transport Cu out of senescing tissues (Himelblau et al, 1998;Mira et al, 2001). nakr1-1 seedling growth (for 2 weeks) was not affected more than the wild type when Zn 2+ (up to 15 mM) or Cu 2+ (up to 25 mM) was included in the growth medium (data not shown).…”
Section: Nakr1 Function As a Metal Binding Proteinmentioning
confidence: 99%